2014
DOI: 10.1589/jpts.26.437
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Obstacle Training in Water on Static Balance of Chronic Stroke Patients

Abstract: [Purpose] This study evaluated the effects of water and land-based obstacle training on static balance of chronic stroke patients. [Subjects] The subjects were randomly allocated to an aqua group (n=15) and a land group (n=15). [Methods] Both groups trained for 40 minutes, 3 times a week for 12 weeks. Static balance was assessed by measuring the mean velocities of mediolateral (ML) and anteroposterior (AP), and sway area with the eyes closed. [Results] Following the intervention, both groups showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
47
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 16 publications
1
47
1
4
Order By: Relevance
“…Most of the research on quiet standing makes use of a kinetic measurement method in which the anterior-posterior and medial-lateral displacements of the COP are calculated on a force platform 11 ) . In general, evaluation of balance ability of stroke patients depends on the following four indices: mean COP velocity (velocity), area of the 95% confidence ellipse (area), average anterior-posterior displacement (Ymean), and average medial-lateral displacement (Xmean) 12 , 13 , 14 , 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research on quiet standing makes use of a kinetic measurement method in which the anterior-posterior and medial-lateral displacements of the COP are calculated on a force platform 11 ) . In general, evaluation of balance ability of stroke patients depends on the following four indices: mean COP velocity (velocity), area of the 95% confidence ellipse (area), average anterior-posterior displacement (Ymean), and average medial-lateral displacement (Xmean) 12 , 13 , 14 , 15 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently there has been a rise in the interest in the usefulness of exercises in water for the rehabilitation of post-CVA patients. Most studies comparing the effectiveness of balance training in the water and in a gym showed that better results were achieved during balance training in water [54,[60][61][62][63].…”
mentioning
confidence: 99%
“…Meanwhile, when exercising in water, its physical characteristics (hydrostatic pressure, the lift force, and high density) reduce the patients' fear of falls and injuries [60,61]. Water has a specific mechanical effect on the body, reducing pain, peripheral edemas, the activity of the sympathetic nervous system, and biomechanical muscle and joint tension, and improving proprioception, which creates better conditions for rehabilitation [60,63] The results of the studies conducted by Kog Noh et al, Han et al, Lee et al, and Jung et al evaluating the effectiveness of balance training in water and in a gym showed that balance training in water was more effective, and the difference, compared to balance training in a gym, was statistically significant [54,60,62,63].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…최근 이런 훈련들을 지상에서 수행 하기 어려운 환자들을 대상으로 수중에서 실시하고 있다 [6]. 수중 치료는 부력, 정수압, 물의 점성, 와류 와 같은 수중 환경의 특성을 이용한 치료로 체중 부하를 최소화하여 관절에 부담을 주지 않고 근력, 지구력 등을 향상시킬 수 있으며 [7] 자세를 보조해 줄 수 있고 항 중력 움직임을 촉진시켜 지상에서 수행하기 어려운 움직임을 수행 할 수 있는 기회를 제공해 준다 [8]. 최근 수중 치료가 신체적으로 장애 를 가진 환자에게 사용되고 있으며 유연성, 관절가 동 범위 및 근력 증진 [9], 호흡 능력 [10], 보행 [11], 대단위 운동 기능 [12] …”
unclassified